2004
DOI: 10.1080/00207590344000367
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the perceived acculturation context of young Moroccans in the Netherlands

Abstract: The goals of this research were twofold: (1) to explore the structure of the perceived acculturation context in a group of 155 Moroccan adolescents and young adults living in the Netherlands, and (2) to examine to what extent this structure can predict quality of relationships, success, and mental health. The perceived acculturation context turned out to be multidimensional and its dimensions independent. The perceived mainstream context consisted of a tolerance factor and an integration factor while the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Lastly, the final research question examines the relationship between the variables for the sample of Albanian-Americans in terms of moderating variables of gender, length of residency in the U.S., and ethnicity of the spouse and mediating variables of employment and education. A study by Ait Ouarasse & Van de Vijver (2004a, 2004b has shown that demographic variables (such as education) mediated the relationship between acculturation and psychological well-being. In addition, education and employment also mediated the relationship between ethnic identity and psychological well-being.…”
Section: Hypothesesmentioning
confidence: 99%
“…Lastly, the final research question examines the relationship between the variables for the sample of Albanian-Americans in terms of moderating variables of gender, length of residency in the U.S., and ethnicity of the spouse and mediating variables of employment and education. A study by Ait Ouarasse & Van de Vijver (2004a, 2004b has shown that demographic variables (such as education) mediated the relationship between acculturation and psychological well-being. In addition, education and employment also mediated the relationship between ethnic identity and psychological well-being.…”
Section: Hypothesesmentioning
confidence: 99%
“…Perceived acculturation expectations are a strong predictor of individual acculturation orientations and outcomes (Ouarasse & Van de Vijver, 2004). Parents' acculturation expectations and ethnic identity, in particular, have been found to be closely linked with their children's acculturation orientations and ethnic identity in a variety of settings, age, and ethnic groups (Dimitrova, Ferrer-Wreder, & Trost, 2015;Nauck, 2001a;Sabatier, 2008;Schachner et al, 2014a).…”
Section: Family-related Conditions For Acculturation and Adjustmentmentioning
confidence: 99%
“…Such individuals are likely to show 'separation' tendencies (Berry 1980), placing high value on holding onto their heritage culture and avoiding interactions with other cultures. In the context of social media engagement, such individuals may have strong preferences for communicating in their own languages and in networking with people of their cultural backgrounds because they benefit from their ethnic communities' resources (Quarasse and van de Vijver 2004) that are available on social media. Therefore, our first hypothesis states: H1: Separation in language preference on social media is a) positively associated with enculturation and b) negatively with associated with acculturation.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…An immigrant who uses an integration strategy may use his or her own language in a private domain (e.g., with family and friends) and the host culture's language while in public (e.g., at work, at school, at a community center), allowing space for both their heritage culture and the host culture (Quarasse and van de Vijver 2004;Yagmur 2014;Yagmur and van de Vijver 2012).…”
Section: Hypotheses Developmentmentioning
confidence: 99%